Pengaruh Perceived Value dan Brand Image Terhadap Repurchase Intention Melalui Word Of Mouth Sebagai Variabel Intervening Smartphone Samsung Galaxy Series - Maya Anggaeni; Naili Farida; Sari Listyorini (Universitas Diponegoro, 2015)
This research is motivated their smartphone trends in society as well as themore famous brand Samsung in the community. In addition to improvements in thebrand image of Samsung, Samsung also increased sales both at the global level as wellas in Indonesia, however, the increased sales of Samsung have not made the Samsungranked number one in the Top Brand Index from 2012 to 2014. The sample are 100person of smartphone Samsung Galaxy consumers. The results showed that the effect ofpartially or simultaneously between Perceived Value and Brand Image on Word ofMouth. Based on a two-stage regression results indicate that Word of Mouth is anintervening variable to variable Repurchase Intention in this study.